PENGEMBANGAN MODUL MATEMATIKA BERBASIS REALISTIK TERINTEGRASI HIGHER ORDER THINKING SKILLS (HOTS) PADA MATERI BANGUN RUANG - Achmad Chuseri; Titi Anjarini; Riawan Yudi Purwoko (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2021)
Learning media is an important tool in learning proces, especially learning media that are made based on student needs and characteristics. One of learning media that is effectively applied at the primary school level is a module. This study aims to produce and determine the feasibility of mathematics learning media in the form of HOTS integrated realistic-based modules on volume building materials (cubes and blocks) as learning media for fifth grade elementary school students. The subjects of study were six students of grade V SD Negeri Sindurjan. The research method was used R&D (Research and Development) using ADDIE model. The ADDIE model consists of analysis, design, development, implementation, evaluation. Based on the results of research (1), a HOTS integrated realistic mathematics module development product is produced. (2) The validation results obtained from the evaluation of media experts by 3.20 and material experts by 3.65. From the two results, it was developed to be 3.40 or > 3.25, the very valid category. (3) The practicality questionnaire was obtained from the student response assessment of 3.40 or > 3.25 with the very practical category. Thus the HOTS integrated realistic-based mathematics module is suitable for use as a learning medium for fifth grade elementary school students.